Analisis Tindak Tutur Ilokusi Direktif Dalam Teks Editorial Pada “Surat Kabar Kompas” Dalam Kaitannya Dengan Pembelajaran Bahasa Indonesia - Ahmad Idham Kholid; Hanuun Dhiyaa Putri Ari; Ika Rizki Refima Putri; Citra Ajeng Cendekia; Kejora Padmarani; Asep Purwo Yudi Utomo; Ruly Indra Darmawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
One example of editorial text found in everyday life is in newspapers. Newspapers provide actual information needed by the public through reporting in editorial texts. The newspaper that is often found today is the Kompas Newspaper. In the educational realm, the editorial text in the Kompas Newspaper can be a medium for learning Indonesian. Editorial text in newspapers requires appropriate sentence structure so that readers can understand the meaning of the contents of the newspaper. Thus, sentence structure in editorial texts can be a medium for analyzing directive illocutionary speech acts. This research aims to determine the types of directive illocution speech acts contained in editorial texts in the Kompas Newspaper. The theoretical benefit of this research is to increase insight and information regarding the types of directive illocution speech acts. The practical benefit is being able to understand the meaning of sentences written in newspapers. This research is classified as descriptive qualitative which refers to a theoretical approach in the form of a pragmatic approach. The method in this research is the matching method using listening and note-taking techniques, while the data presentation method uses formal data presentation. The primary data used is editorial text sourced from the Kompas Newspaper. The data that has been found is presented in the form of an explanation and linked to secondary data in the form of similar previous research. The results of this research are 18 types of directive illocution speech acts which include 7 directive illocution speech acts suggesting, 1 opposing, 2 requesting, 1 commanding, 1 hoping, 1 appealing, 1 giving a signal, 2 pleading, 1 urging, and 1 inviting.